Pengaruh Faktor Sosial Ekonomi terhadap Tingkat Fertilitas di Provinsi Jawa Timur - Mahardika Bagus Sugiarto; Fivien Muslihatinningsih; Endah Kurnia Lestari (Jurnal Ekuilibrium, 2021)
The high rate of population growth is a serious obstacle for Indonesia so that success in carrying out development needs to be increased in high quantity so that it can support the rate of growth in the economy. The purpose of this study is to determine and analyze the influence of socio-economic factors on fertility levels in East Java Province. The data used in this study is secondary data obtained from BPS and browsing internet websites as a support. The unit of analysis in this study is the effect of social economic factors on fertility levels. Fertility level is a driving variable and variables from social factors (poverty, health, education, employment, per capita income) in 2014-2018 are independent variables. While the method used in this study is multiple linear regression analysis. The results of this study indicate that poverty no significant positive effect on fertility in East Java. Health has no significant positive effect on fertility in East Java. Education has a significant negative effect on fertility in East Java. Employment has a significant negative effect on fertility in East Java. Income has a significant negative effect on fertility in East Java.